2018
DOI: 10.1371/journal.pone.0196504
|View full text |Cite
|
Sign up to set email alerts
|

GIMAP6 is required for T cell maintenance and efficient autophagy in mice

Abstract: The GTPases of the immunity-associated proteins (GIMAP) GTPases are a family of proteins expressed strongly in the adaptive immune system. We have previously reported that in human cells one member of this family, GIMAP6, interacts with the ATG8 family member GABARAPL2, and is recruited to autophagosomes upon starvation, suggesting a role for GIMAP6 in the autophagic process. To study this possibility and the function of GIMAP6 in the immune system, we have established a mouse line in which the Gimap6 gene can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 64 publications
(101 reference statements)
1
17
1
Order By: Relevance
“…In fact, in addition to their involvement in the regulation of the immune system, GIMAPs might act as tumor suppressor genes, as was speculated by Krucken et al who showed that all GIMAPs are expressed at very low levels in diverse cancer tissues and cell lines 22 . This hypothesis was further confirmed by other studies that proved that GIMAP4 accelerates the execution of programmed cell death 15 , while GIMAP6 plays a role in the autophagic process 23 . On the other hand, a study on non-small cell lung cancer (NSCLC) showed that the expression of GIMAP4, GIMAP6, and GIMAP8 were lower in tumor tissues than in adjacent non-tumor tissues 24 .…”
Section: Discussionsupporting
confidence: 74%
“…In fact, in addition to their involvement in the regulation of the immune system, GIMAPs might act as tumor suppressor genes, as was speculated by Krucken et al who showed that all GIMAPs are expressed at very low levels in diverse cancer tissues and cell lines 22 . This hypothesis was further confirmed by other studies that proved that GIMAP4 accelerates the execution of programmed cell death 15 , while GIMAP6 plays a role in the autophagic process 23 . On the other hand, a study on non-small cell lung cancer (NSCLC) showed that the expression of GIMAP4, GIMAP6, and GIMAP8 were lower in tumor tissues than in adjacent non-tumor tissues 24 .…”
Section: Discussionsupporting
confidence: 74%
“…It also lead to more rapid T cell activation following stimulation by PMA and ionomycin, and the authors showed for the first time that GIMAP6 can function as an ATPase (the only member of the GIMAP family shown to do so) [8]. In 2018, Pascall et al [15,16] established a knockout mouse model of GIMAP6 deficiency and showed that these mice suffered a 50-70% reduction in the numbers of circulating CD4+ and CD8+ lymphocytes as well as reduced autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…GIMAPs are involved in the development, maintenance, and homeostasis of lymphocytes, especially CD4 + T cells and B cells, but also T regulatory cells (Tregs) (53)(54)(55). In the absence of individual GIMAP members, there is progressive lymphocyte loss leading to lymphopenia, poor cell proliferation, and paradoxical autoimmune states because of impaired Treg function (54)(55)(56)(57)(58). A previous gene family analysis showed that the GIMAP family is expanded in the Egyptian rousette compared to a bat ancestor (19), with 14 putative members.…”
Section: Discussionmentioning
confidence: 99%